ChemInform Abstract: Efficient Synthesis of the Cyclopentanone Fragrances (Z)‐3‐(2‐Oxopropyl)‐2‐(pent‐2‐en‐1‐yl)cyclopentanone (I) and Magnolione® (II). Issue 27 (8th July 2014) - Pan, Guojun; Williams, Robert M.
Abstract The asymmetric synthesis of an intermediate which enables the asymmetric syntheses of (I) and (II) is also presented.